2016
DOI: 10.3390/photonics3010004
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Enhanced Modulation Response in Integrated Coupled Cavities DBR Lasers Using Photon-Photon Resonance

Abstract: Abstract:In the last few decades, various solutions have been proposed to increase the modulation bandwidth and, consequently, the transmission bit-rate of semiconductor lasers. In this manuscript, we discuss a design procedure for a recently proposed laser cavity realized with the monolithic integration of two distributed Bragg reflector (DBR) lasers allowing one to extend the modulation bandwidth. Such an extension is obtained introducing in the dynamic response a photon-photon resonance (PPR) at a frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…We present the small signal response including the bandwidth enhancement and chirp reduction dependent on the coupling parameters and the coupling phase tolerance. The bandwidth enhancement and chirp reduction can be explained by the increased frequency of carrier-photon resonance (CPR) due to detuned-loading effect [18,19], and additionally the photon-photon resonance (PPR) at a frequency higher than CPR due to beating between different modes in coupled cavities [20][21][22][23][24][25]. We also present a comparison between the Lang-Kobayashi model and coupled mode model.…”
Section: Introductionmentioning
confidence: 99%
“…We present the small signal response including the bandwidth enhancement and chirp reduction dependent on the coupling parameters and the coupling phase tolerance. The bandwidth enhancement and chirp reduction can be explained by the increased frequency of carrier-photon resonance (CPR) due to detuned-loading effect [18,19], and additionally the photon-photon resonance (PPR) at a frequency higher than CPR due to beating between different modes in coupled cavities [20][21][22][23][24][25]. We also present a comparison between the Lang-Kobayashi model and coupled mode model.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with an opportune design of the active region and RC-parasitic, which shunts the modulation current outside the active region at high frequencies, a high modulation bandwidth can be achieved. Optical feedback has proven to increase the modulation bandwidth of VCSELs, due to an induced photon-photon resonance (PPR) effect [14][15][16][17] . Dalir et al [18,19] demonstrated modulation bandwidth enhancement of the VCSEL via adding a single transverse-coupled-cavity (TCC) to a primary VCSEL cavity.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) In a semiconductor laser coupled with a feedback cavity, the PPR effect is derived by the external feedback cavity. 13) This second high-frequency peak is manifested as a RM peak beyond the bandwidth of the solitary laser, which is determined by the intrinsic carrierphoton resonance (CPR). The authors showed that OFB from a short-coupled-cavity has the potential of inducing PPR manifested as RM over a narrow passband even far beyond the bandwidth frequency.…”
Section: Introductionmentioning
confidence: 99%